THz and IR Spectroscopy of Molecular Systems That Simulate Function-Related Structural Changes of Proteins. Issue 5 (11th July 2012) - Brandt Brandt, N. N. N. N.; Chikishev Chikishev, A. Yu. A. Yu.; Mankova Mankova, A. A. A. A.; Nazarov Nazarov, M. M. M. M.; Sakodynskaya Sakodynskaya, I. K. I. K.; Shkurinov Shkurinov, A. P. A. P.
Abstract : The activity of enzymes in organic solvents substantially increases in the presence of crown ethers. Tris(hydroxymethyl)aminomethane (tris) is chosen as a model compound to simulate the interaction of surface amino groups of proteins with crown ether. The methods of FTIR and time-domain THz spectroscopy are used to study the interaction of tris with 18-crown-6. The THz spectra of the complexes are measured for the first time.